Heterogeneous attention to inflation and monetary policy - Ekaterina Shabalina; Mary Tzaawa-Krenzler (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2025)
We study how heterogeneous attention to inflation across households affects the transmission of monetary policy. Using household-level surveys for the US and Australia, we first show that households' attention to inflation varies across income levels. Specifically, we find that high-income households pay more attention to inflation than other income groups. To quantify the effects for the aggregate economy, we build a Heterogeneous Agent New Keynesian model with an endogenous attention choice where the level of attention to inflation varies along the income distribution. Compared to fully rational inflation expectations, we find that the economy faces a less severe recession after a monetary policy tightening when households' expectations are stable. This result is driven by the misperceived fall in future real labor income of low-income households that incentivizes an increase in their labor supply. At the same time, in response to the tightening, low-earners experience an even larger decrease in their welfare under inattention compared to the rational expectations case.
Keywords: D84; D91; E21; E71; E52; 330; Inattention; HANK; Monetary Policy; Inflation Expectations